La compraventa sobre el bien ajeno en el Perú y sus fuentes: ¿validez o ineficacia? - Villota Cerna, Marco Antonio (Pontificia Universidad Católica del Perú, 2022)
This article deals with the trading of other’s property in Peru as to whether it constitutes a case of invalidity or ineffectiveness of the contract, based on the different jurisprudence and doctrine that has been produced on the matter. This is based on a historical and comparative study of the contract of sale in Roman Law and in the various civil law legislations, including the figure of the sale of another’s property and the treatment of the registry rules. In the case of Peru, the influence of comparative law in the regulation of the sales contract is analyzed and how it has influenced the different interpretation of the sale of another’s property and the registry rules. Additionally, an analysis is made of the different cases of sale and purchase of another’s property, the corresponding remedies, the concordance with the registry rules; and finally, the corresponding conclusions are drawn.

El presente artículo trata sobre la compraventa de bien ajeno en el Perú respecto a si constituye un supuesto de invalidez o de ineficacia del contrato, a propósito de la diversa jurisprudencia y doctrina que se ha producido sobre la materia. Para ello se parte de un estudio histórico y comparativo del contrato de compraventa en el Derecho Romano y en las diversas legislaciones del civil law, incluida la figura de la venta de bien ajeno y el tratamiento de las normas registrales. En el caso del Perú, se analiza la influencia del derecho comparado en la regulación del contrato de compraventa y cómo ha incidido en la diferente interpretación de la compraventa de bien ajeno y en las normas registrales. Adicionalmente, se hace un análisis de los diferentes supuestos de compraventa de bien ajeno, los remedios que corresponden, la concordancia con las normas registrales; y finalmente se extraen las correspondientes conclusiones.
The trading of other’s property in Peru and its sources: validity or inefficiency?
Keywords: Compraventa de bien ajeno; Validez; Ineficacia; Oponibilidad de Derechos; Non domino; Derecho Romano; Civil Law; Trading of other’s property; Validity; Ineffectiveness; Opposability of Rights; Non domino; Roman Law; Civil Law; https://purl.org/pe-repo/ocde/ford#5.05.00